2017
DOI: 10.1186/s12890-017-0527-y
|View full text |Cite
|
Sign up to set email alerts
|

Access to affordable medicines and diagnostic tests for asthma and COPD in sub Saharan Africa: the Ugandan perspective

Abstract: BackgroundEquitable access to affordable medicines and diagnostic tests is an integral component of optimal clinical care of patients with asthma and chronic obstructive pulmonary disease (COPD). In Uganda, we lack contemporary data about the availability, cost and affordability of medicines and diagnostic tests essential in asthma and COPD management.MethodsData on the availability, cost and affordability of 17 medicines and 2 diagnostic tests essential in asthma and COPD management were collected from 22 pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 9 publications
0
61
0
Order By: Relevance
“…Spirometry may be a good alternative that gives insight into the pulmonary status, however, discoordination due to muscle weakness and ataxia will often underestimate true lung function. Compared to other diagnostic tests described here, spirometry is relatively easy accessible and affordable but still not available in all hospitals [54]. In our experience, most patients have a restrictive pattern (explaining a low forced vital capacity), sometimes combined with obstructive pulmonary dysfunction.…”
Section: Pulmonologymentioning
confidence: 89%
“…Spirometry may be a good alternative that gives insight into the pulmonary status, however, discoordination due to muscle weakness and ataxia will often underestimate true lung function. Compared to other diagnostic tests described here, spirometry is relatively easy accessible and affordable but still not available in all hospitals [54]. In our experience, most patients have a restrictive pattern (explaining a low forced vital capacity), sometimes combined with obstructive pulmonary dysfunction.…”
Section: Pulmonologymentioning
confidence: 89%
“…Despite these corrective measures, the "corrected" European standards continue to significantly overestimate the predictive ventilatory variables in Beninese subjects. Similarly, Dufetel et al (1990) showed in Africa that the total lung capacity among Togolese (in West Africa) men aged 25 to 55 years was lower by an average of 25%, and the other lung volumes were also 22% lower than those men of the same age and size [31] [32]. In this context, the authors concluded that it would be wrong to use a proportionality factor to define the reference spirometric values for black children based on the standards defined for Caucasian subjects [31] [32].…”
Section: Comparisons Of Our Standard Values With Those Of Ers-93mentioning
confidence: 99%
“…Similarly, Dufetel et al (1990) showed in Africa that the total lung capacity among Togolese (in West Africa) men aged 25 to 55 years was lower by an average of 25%, and the other lung volumes were also 22% lower than those men of the same age and size [31] [32]. In this context, the authors concluded that it would be wrong to use a proportionality factor to define the reference spirometric values for black children based on the standards defined for Caucasian subjects [31] [32]. The question then arises to know why, despite the ethnic corrections integrated into spirometers imported from Europe, the ventilatory variables measured in black African subjects are higher than those of their Caucasian counterparts of the same age, sex and height?…”
Section: Comparisons Of Our Standard Values With Those Of Ers-93mentioning
confidence: 99%
See 1 more Smart Citation
“…COPD is the second leading cause of death in Nepal 4. COPD management in low/middle-income countries is suboptimal with diagnostic tests and medications largely unavailable or unaffordable for most people 5. Additionally, prior research has documented gaps in mid-level providers’ diagnostic and clinical decision-making skills in similar settings in Nepal6 and India 7…”
Section: Introductionmentioning
confidence: 99%